STUDI KELAYAKAN INDUSTRI RUMAH TANGGA SARI KEDELAI âBU ADEâ DI YOGYAKARTA - , AGNES WAHYUMARLITA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study was to determine the feasibility of household soymilk industry and know the problems faced and efforts to overcome them. The research, at household soymilk industry "Bu Ade" which was located at Jalan Panuluh 379A, Pringwulung, Yogyakarta, method used was descriptive. The data used are primary and secondary data. Data collection techniques were observation, interview, and record keeping. The results showed that the value of R/C>1,08, capital profitability value of Ï/C ie 7,90, profit margin value of Ï/R ie 4,85%, and coefficient of variation obtained was smaller than the standard coefficient of variation, namely 0,06<0,5. Breakeven analysis showed that the soymilk production was higher than the value of the BEP, 10.647,92 units/month>9168,73 units/month, industry acceptance of household soymilk was greater than the BEP value, Rp 26.619.791,67/month>Rp 22.921.823,85/month, and soya prices was also above the BEP value, Rp 2.500,00/unit>Rp 2.300,90/unit. Thus the household industry of soymilk "Bu Ade" in Yogyakarta could be said to be beneficial and feasible to develop. The results showed that the sensitivity analysis of soybean price increases (input) up to 71% was still profitable. Analysis of changes in the price of soymilk products (output) showed that if there was price decrease of 7,96%, the household industry of soymilk suffered losses.